Предмет: Алгебра,
автор: malish2249
Разложить на множители n^2(3n-4)^2+(4-3n)
Ответы
Автор ответа:
0
Известно, что (a - b)² = (b - a)²
n²(3n - 4)² + (4 - 3n) = n²(4 - 3n)² + (4 - 3n) = (4 - 3n)(n²(4 - 3n) + 1) = (4 - 3n)(4n² - 3n³ +1)
n²(3n - 4)² + (4 - 3n) = n²(4 - 3n)² + (4 - 3n) = (4 - 3n)(n²(4 - 3n) + 1) = (4 - 3n)(4n² - 3n³ +1)
Похожие вопросы
Предмет: Литература,
автор: dimacyb17
Предмет: Математика,
автор: leyliahad
Предмет: Алгебра,
автор: pineginaksenia1
Предмет: Литература,
автор: tomacool774
Предмет: Математика,
автор: Аноним